Biodegradation of phthalate esters by Paracoccus kondratievae BJQ0001 isolated from Jiuqu (Baijiu fermentation starter) and identification of the ester bond hydrolysis enzyme. (August 2020) - Xu, Youqiang; Minhazul, Karim A.H.M.; Wang, Xiaocheng; Liu, Xiao; Li, Xiuting; Meng, Qi; Li, Hehe; Zhang, Chengnan; Sun, Xiaotao; Sun, Baoguo
Abstract: Phthalate ester (PAE) pollution is an increasing problem globally. Paracoccus kondratievae BJQ0001 was isolated from the fermentation starter of Baijiu and showed an efficient degradation capability toward PAEs. To our poor knowledge, this is the first report of a P . kondratievae strain capable of degrading PAEs. The first complete genome sequence of P . kondratievae was presented without gaps, and composed of two circular chromosomes and one plasmid. The species simultaneously degraded di-methyl phthalate (DMP), di-ethyl phthalate (DEP), di-butyl phthalate (DBP), di-isobutyl phthalate (DIBP) and di-(2-ethylhexyl) phthalate (DEHP), with DMP and DEP as the preferred substrates. The half-life ( t 1/2 ) of DMP was only 6.34 h with an initial concentration of 200 mg/L. Combined with gene annotation and metabolic intermediate analysis, a metabolic pathway was proposed for the species. Benzoic acid, the intermediate of anaerobic PAE metabolism, was identified in the aerobic degradation process. Two key enzymes for alkyl ester bond hydrolysis were obtained, and belonged to families IV and VI of hydrolases, respectively. These results will promote the investigation of PAE degradation by P . kondratievae, and provide useful information for improving the quality control of food and environmental PAE treatment. Graphical abstract: Image 1 Highlights: A Paracoccus kondratievae strain isolated from Baijiu efficiently degraded PAEs. The first complete genome sequence was assembled with 2 chromosomes and 1 plasmid. An anaerobic metabolic intermediate was identified during aerobic PAE degradation. One alkyl ester bond hydrolysis enzyme was belonged to the IV family of hydrolases. The microbial and metabolic diversity of PAE-degrading bacteria was indicated. Abstract : A Paracoccus kondratievae strain was first reported for degrading phthalate esters (PAEs), together with its first complete genome, PAE metabolic pathway and key enzyme for hydrolysis.